Central Concentration and Escape of Ionizing Photons in Galaxies at the Epoch of Reionization - Cheqiu Lyu; Enci Wang; Junxian Wang; Cheng Jia; Jie Song; Yangyao Chen; Zeyu Chen; Haoran Yu; Chengyu Ma; Jinyang Wang; Yifan Wang; Xu Kong (The Astrophysical Journal Letters)
Compact, low-mass galaxies with strong nebular emission are considered promising candidates for efficient ionizing photon production and escape. We present a spatially resolved analysis of 189 galaxies at redshifts z ∼ 6.7–7.6 in JADES GOODS-N and GOODS-S fields and selected via JWST/NIRCam F410M filter. By employing annular photometry and spectral energy distribution fitting across rest-frame UV to optical wavelengths, we investigate the internal structure of star formation, ionizing photon production and escape, as well as the resolved star formation histories within these galaxies. We find that these galaxies exhibit compact, centrally concentrated, and bursty star formation, especially in lower-mass systems ( ${log}\,M_{* }/M_{\odot }\lt 9.0$ ). The central regions of them display extreme [O III ]+H β equivalent widths (>1000 Å), high ionizing photon production efficiencies ( ξ _ion ∼ 10 ^25.6 Hz erg ^−1 ), steep UV slopes (∼−2.3), and elevated escape fractions ( f _esc > 0.08), with all these properties peaking in the inner regions. These findings reveal outside-in growth and rising star formation histories at z ∼ 7, with the central regions of them playing a pivotal role in driving cosmic reionization.